A study of the monthly and hourly frequencies of the phenomenon of suspended dust in selected stations in Iraq (Journal of the College of Basic Education, 2023)
In this research, the monthly and hourly recurrences of the phenomenon of suspended dust, which is symbolized intertwined by the code number (06) in the ritual code, were studied in selected stations in Iraq (Mosul, Baghdad, Basra) for the period (1995-2005) by using the data of the General Assembly. Iraqi meteorological and seismic monitoring.The results showed that the summer months (June, July, August), and the spring months (March, April, May) recorded the highest value for the number of occurrences of suspended dust, while the lowest value for the number of occurrences of suspended dust was recorded in the winter months (December, January February), and the autumn months (September, October, November) and in all three study stations.The results also showed that the daytime weather observations (, , ,) and according to Kering International Time () recorded the highest rate of suspended dust, while the evening weather observations (, , ), recorded the lowest rate of suspended dust in all three study stations.